Slayers [videorecording (DVD)] - Jane, Thomas; Breslin, Abigail, 1996-; Akerman, Malin, 1978-; Hayward, Kara, 1998-; Levin, K. Asher; Levin, K. Asher; Imbrogno, Zack (Decal, 2022)
Kick-butt vampire slayer, Elliot Jones, has one mission in life to find the vampire who murdered his teenage daughter, and tonight he'll finally have his revenge. But he'll need the help of a crew of social media superstars.